Analisis Kebijakan Ghana Menangani Digital Dumping Ground di Agbogbloshie - Purnama, Oliex Candra; Putranti, ika Riswanti (Journal of International Relations, 2019)
As technology develops, the need for information technology devices increases. It wouldalso increase the electronic waste products. This study aims to describe how the policies andactions of the Ghanaian government dealing with e-waste issues. Based on the data collected,Ghana to receive e-waste from many different development countries. Ghana, in the city ofAgbogbloshie is the largest digital dumping ground in the world. E-waste is a hazardous wastethat has a long-term impact on society and the environment. In this study, authors used theDescriptive research method. This research is problem solving that investigated and analyzed bydescribing the subject or object of state, person, institution, society and others. The author foundthat Ghana is implementing a prefentive policy strategy and conducts more detailed oversight indealing with e-waste. Nevertheless, in 2016 Ghana has become the largest landfill in the world.In addition, Ghana has also conducted several collaborations in dealing with e-waste with othercountries such as China, Israel and the United Kingdom.